TINJAUAN SYARIAH TERHADAP TRANSAKSI MUAMALAT ASURANSI KESEHATAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) - Kolistiawan, Budi (IAIN Tulungagung, 2016)
Insurance business can be distinguished on some reviews. It includes general insurances, life insurances and reinsurances (on the basis of its function). Based on its basic policy, It includes term life insurances, whole life insurances, two benefcial insurances, insurances of investment unit (unit linked). Based on its belongings, it includes national private-owned insurances, state-owned insurances, foreign corporations-owned insurances, and multiplicity-owned insurances. Based on the nature of its implementation, it includes voluntary and compulsory insurances. Based on the business support activities, it includes insurance brokers, reinsurance brokers, insurance loss assessor, consulting actuary, and insurance agents. Mean while, mechanisms of Takaful (shariâa insurances) include underwriting, insurance policies, premiums, management of premiums, claims and insurance coverage. The main obstacles to develop shariâa insurance are lack of socialization, limitation of human resources of Takafulâs expert; lack of Muslim support, weakness of government support.Keywords: Insurance, Syariâah, BPJS.